Entrepreneurial University Accelerator Innitiative - Abdul Ghonisyah, Ghaling Achmad; Kusmayadi, Andri; Sumaryana, Yusuf (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
This community service activity was carried out through the Entrepreneurial University Accelerator Initiative programme designed to develop the entrepreneurial skills of Universitas Perjuangan Tasikmalaya Management students. The programme was conducted in the form of a bootcamp that focused on making products from melon-based ingredients, aiming to improve students' competence in product innovation and entrepreneurship based on local ingredients. A total of 5 students were actively involved in this bootcamp, which lasted for 5 days with a series of training that included understanding the product value chain, production techniques, marketing, and market analysis. Through evaluation, 85% of students were able to produce market-ready product prototypes, such as melon juice, jam, and melon-based healthy snacks. In addition, 92% of participants showed significant improvement in their understanding of marketing and product development strategies. The results of this programme showed success in encouraging students' creativity and entrepreneurial skills based on local potential. Overall, the programme had a positive impact in equipping students with relevant skills to face labour market challenges and strengthening the entrepreneurial ecosystem in the academic environment.